A piezoelectric active sensing method for quantitative monitoring of bolt loosening using energy dissipation caused by tangential damping based on the fractal contact theory - Wang, Furui; Huo, Linsheng; Song, Gangbing (Smart materials and structures, 2018)
Monitoring of bolt looseness is essential for ensuring the safety and reliability of equipment and structures with bolted connections. It is well known that tangential damping has an important influence on energy dissipation during wave propagation across the bolted joints, which require different levels of preload. In this paper, the energy dissipation generated by tangential damping of the bolted joints under different bolt preloads was modeled analytically based on fractal contact theory, which took the imperfect interface into account. A saturation value exists with the increase of the bolt preload, and the center frequency of emitted signal is demonstrated to affect the received energy significantly. Compared with previous similar studies based on experimental techniques and numerical method, the investigation presented in this paper explains the phenomenon from the inherent mechanism, and achieves the accurate quantitative monitoring of bolt looseness directly, rather than an indirect failure index. Finally, the validity of the proposed method in this paper was demonstrated with an experimental study of a bolted joint with different preload levels.